AMINA WADUD MUHSIN GENDER THINKING IN THE HERMENEUTIC PERSPECTIVE OF HANS GEORG GADAMER - Muh. Yasin Yasin Nur; Indo Santalia; Muhaemin Latif (Pascasarjana UIN Alauddin Makassar, 2021)
The purpose of this study is to find out the gender thinking of Amina Wadud Muhsin in the view of Hans Georg Gadamer's Hermeneutics. This research is library research using a research approach, namely: philosophical, grammatical, linguistic and phenomenological approaches. Then the source of this research data is taken from books, articles and journals related to the thoughts of Amina Wadud with Gadamer. Furthermore, the data analysis method used is descriptive method, content analysis, interpretation method, comparison, taxonomy. The results of this study indicate that: First, related to Amina Wadud's gender thinking, namely: 1. The creation of humans. According to Amina Wadud that the origin of humans, both male and female, comes from one nafs which is part of the paired system. 2. Leader. Amina Wadud strongly rejected Qawwamun to be limited to the position of men compared to women. However, there must be harmony, so Amina Wadud proposes a new idea, namely the